Exploring Norms in Agile Software Teams - Stray, Viktoria; Fægri, Tor Erlend; Moe, Nils Brede (Product-Focused Software Process Improvement, 2016)
The majority of software developers work in teams and are thus influenced by team norms. Norms are shared expectations of how to behave and regulate the interaction between team members. Our aim of this study is to gain more knowledge about team norms in software teams and to increase the understanding of how norms influence teamwork in agile software development projects. We conducted a study of norms in four agile teams located in Norway and Malaysia. The analysis of 22 interviews revealed that we could extract a varied set of both injunctive and descriptive norms. Our results suggest that team norms have an important role in enabling team performance.